Global norms and local action: the campaigns to end violence against women in Africa - Medie, Peace A. (Oxford studies in gender and international relations, 2020)
When and why do states implement international women's rights norms? Global Norms and Local Action is an examination of states' responses to violence against women (VAW) in Africa and their implementation of the international women's justice norm. Despite the presence of laws on various forms of VAW in most African countries, most victims face barriers to accessing justice through the criminal justice system. This problem is particularly acute in post-conflict countries. International organizations such as the United Nations, and women's rights advocates have, therefore, promoted the international women's justice norm, which emphasizes the establishment of specialized mechanisms within the criminal justice sector to address VAW. With a focus on the response of the police to rape and intimate partner violence in post-conflict Côte d'Ivoire and Liberia, this book theorizes the United Nations' and women's movements' influence on the implementation of the international women's justice norm. It draws on over 300 interviews in both countries to demonstrate that strong international and domestic pressures, combined with favourable political and institutional conditions, are key to the rapid establishment of specialized mechanisms within the police force and to how police officers respond to rape and intimate partner violence cases. It argues that despite significant weaknesses, specialized mechanisms have improved women's access to justice. The book concludes with suggestions for how domestic and international human rights organizations, policymakers, and women's rights advocates can contribute to a holistic approach to addressing VAW.